Negative electrode composition containing organic sulfur binder

By using the water-soluble polymer P prepared by using organic sulfur monomers as a binder in the negative electrode composition and combining metal or carbon graphite materials to form an efficient aqueous negative electrode composition, the shortcomings of the negative electrode composition in the prior art in terms of mechanical strength and electrochemical resistance are solved, and better component compatibility and preparation efficiency are achieved.

CN119522243APending Publication Date: 2025-02-25COATEX SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380056186.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-07-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The negative electrode compositions in the prior art have shortcomings in terms of mechanical strength and electrochemical resistance stability, and the reduction of component compatibility and component quantity during the preparation process is difficult to achieve.

Method used

An aqueous negative electrode composition containing water-soluble polymer P is used, and a polymer P prepared by using the organic sulfur monomer M is used as the binder L, and combined with metal fibers, metal particles, carbon graphite fibers or carbon graphite particles as material E, to form an efficient negative electrode composition.

Benefits of technology

The mechanical strength and electrochemical resistance stability of the negative electrode are improved, the compatibility of components is enhanced, and the number of components during the preparation process is reduced, while achieving uniform conductive layer formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to an aqueous negative electrode composition comprising metal particles or metal fibres or carbon graphite particles or carbon graphite fibres and a binder comprising at least one water-soluble polymer P prepared on the basis of organosulfur monomers. The invention also relates to a method for producing a negative electrode using said aqueous composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to an aqueous negative electrode composition comprising metal particles or metal fibers or carbon graphite particles or carbon graphite fibers and a binder, wherein the binder comprises at least one water-soluble polymer P prepared using an organic sulfur monomer. The present invention also relates to a method for producing a negative electrode using the aqueous composition.

[0002] Known negative electrode compositions generally comprise carbon or metal in particle form combined with a binding composition. This binding composition must be able to effectively bind the carbon or metal to a substrate to form a negative electrode. The most common binding composition comprises a styrene-butadiene polymer. This composition is able to fix the particles on a metal substrate. Therefore, when using these negative electrode compositions to produce negative electrodes, the binding properties are decisive. In addition, mechanical strength or electrochemical resistance stability is particularly sought.

[0003] The negative electrode composition must be easily and uniformly applied in order to obtain a uniform layer on the negative electrode surface and to limit defects or avoid them in order to obtain a uniform and particularly efficient conductive layer.

[0004] Typically, the adhesive composition also contains various additives, such as thickeners, dispersants, such as cellulose derivatives. The most common cellulose derivatives are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxymethyl cellulose.

[0005] These negative electrode compositions usually contain silicon to increase the capacity of the prepared negative electrode. During the charge-discharge cycle of batteries containing these negative electrodes, strain is usually observed, which can lead to irreversible changes in the negative electrode, especially due to the increase in silicon volume. Therefore, strain tolerance is also a desired property.

[0006] When preparing negative electrode compositions, it should be possible to reduce the number of ingredients used.

[0007] The compatibility of the different components of the negative electrode compositions is also an important factor when preparing negative electrode compositions and using these compositions to prepare negative electrodes.

[0008] The document EP 3214676 discloses a slurry for preparing a negative electrode for a secondary lithium-ion battery, which contains a water-soluble polyacrylic acid copolymer. The document WO 2014024937 describes a secondary battery negative electrode prepared using a binder and a fluorinated, sulfonated polymer. The document WO 2015008626 describes a poly(meth)acrylamide binder for battery preparation, having a weight-average molecular weight of 300,000 g / mol to 6,000,000 g / mol. The document KR 20210064944 describes a copolymer made of PVDF and styrene sulfonic acid.

[0009] The negative electrode compositions in the prior art are not always satisfactory. Therefore, there is a need for a negative electrode composition that provides a solution to all or part of the problems of the negative electrode compositions in the prior art.

[0010] Therefore, the present invention provides an aqueous negative electrode composition, which comprises, relative to the total dry weight of the binder L and the material E:

[0011] * 0.5 to 15% by dry weight of at least one binder L comprising at least one water-soluble polymer P having a weight average molecular weight Mw (measured by SEC) of 2000 to 1000000 g / mol, wherein the water-soluble polymer P is prepared by polymerization of at least one organic sulfur monomer M in the presence of at least one initiator compound, and

[0012] * 85% to 99.5% by dry weight of at least one material E selected from metal fibers, metal particles, carbon graphite fibers, carbon graphite particles, silicon particles, and combinations thereof.

[0013] Basically, for the present invention, the polymer P is prepared using monomers M which are organic sulfur compounds. The monomers M comprise non-inorganic sulfur in combination with at least one organic residue, preferably in combination with a hydrocarbon residue which may contain one or more than one heteroatom, such as oxygen or nitrogen or even phosphorus. Preferably according to the present invention, the monomers M are selected from sulfonated monomers M1, sulfated monomers M2 and combinations thereof. According to the present invention, the sulfonated monomers M1 comprise at least one compound of the formula SO 3 - sulfonate ions or groups, the sulfated monomer M2 comprises at least one of the formula SO 4 - More preferably according to the present invention, the monomer M is a sulfonated monomer M1.

[0014] According to the invention, the monomer M further comprises at least one polymerizable group, preferably at least one ethylenically unsaturated group, in particular a methacrylate group, an acrylate group, a methacrylamide group, an acrylamide group, a styrene group, an allyl group, a methallyl group, an isoprene group or a vinyl group.

[0015] According to the invention, the organosulfur monomer M is particularly preferably selected from the group consisting of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), allylsulfonic acid, alkylenesulfonates, alkylenearylsulfonates, in particular styrenesulfonates, vinylsulfonates, methallylsulfonates, allylsulfonates, methallylsulfonates, allylsulfonates, methallylsulfates, allylsulfates, 2-sulfoethylmethacrylate, 3-allyloxy-2-hydroxy-1-propanesulfonic acid, 3-sulfopropylmethacrylate, salts thereof and combinations thereof. Preferred monomers M are the sodium salt of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), the sodium salt of 3-allyloxy-2-hydroxy-1-propanesulfonic acid and sodium styrenesulfonate, in particular the sodium salt of 2-acrylamido-2-methylpropanesulfonic acid (AMPS).

[0016] Advantageously according to the invention, when preparing the polymer P, only the monomer M can be used. Preferably according to the invention, the monomer M can be combined with at least one other monomer, preferably with at least one other monomer selected from anionic monomers, nonionic monomers and combinations thereof. Still more preferably, the monomer M can be combined with at least one other anionic monomer.

[0017] Preferably according to the present invention, monomer M can be combined with at least one other anionic monomer M3, and the anionic monomer M3 is selected from acrylic acid, methacrylic acid, acrylate, methacrylate, maleic acid, maleate, itaconic acid, itaconic acid salt, crotonic acid, crotonate, acrylic acid oligomer and a combination thereof. More preferably according to the present invention, monomer M can be combined with at least one other anionic monomer M3, and the anionic monomer M3 is selected from acrylic acid, methacrylic acid, acrylate, methacrylate and a combination thereof. Preferably according to the present invention, relative to the total weight of the monomers, the amount of monomer M3 is 2% to 98% by weight, preferably 5% to 90% by weight or 15% to 85% by weight.

[0018] It is also preferred according to the invention that the monomer M can be combined with at least one other nonionic monomer M4 selected from vinyl acetate, C of compounds derived from an acid selected from acrylic acid, methacrylic acid, maleic acid, itaconic acid and crotonic acid. 1 To C 8 Esters (ethyl methacrylate, methyl methacrylate, butyl methacrylate, ethyl acrylate, methyl acrylate, butyl acrylate), hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, amino monomers (acrylonitrile, vinyl lactam), styrene and combinations thereof. More preferably according to the present invention, monomer M may be combined with at least one other nonionic monomer M4 selected from vinyl acetate, C of compounds derived from an acid selected from acrylic acid, methacrylic acid, maleic acid, itaconic acid and crotonic acid. 1 To C 8Esters (ethyl methacrylate, methyl methacrylate, butyl methacrylate, ethyl acrylate, methyl acrylate, butyl acrylate), hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, styrene and combinations thereof. Further preferably according to the present invention, monomer M can be combined with at least one other nonionic monomer M4, and the nonionic monomer M4 is selected from ethyl acrylate, methyl acrylate, butyl acrylate, styrene and combinations thereof.

[0019] According to the present invention, preferably, the amount of monomer M4 used is 2 to 30 wt %, preferably 5 to 25 wt % or 10 to 20 wt %, relative to the total weight of the monomers.

[0020] According to the invention, the polymer P is preferably prepared in the absence of acrylamide monomers or acrylamide derivatives, in particular in the absence of acrylamide, methacrylamide, dimethylacrylamide, diethylacrylamide and N-methylolacrylamide.

[0021] It is also preferred according to the invention to prepare the polymer P in the absence of crosslinking monomers and in the absence of halogenated monomers, in particular in the absence of fluorinated monomers.

[0022] It is also preferred according to the present invention to prepare the polymer P using the following combinations: a combination of monomer M and monomer M3, a combination of monomer M and monomer M4, a combination of monomer M, monomer M3 and monomer M4.

[0023] More preferably, according to the present invention, the polymer P is prepared using the following combinations: a combination of monomer M1 and monomer M3, a combination of monomer M1 and monomer M4, a combination of monomer M1, monomer M3 and monomer M4.

[0024] If additional monomers are used in the preparation of the polymer P, the proportion of the monomer M and the proportion of the additional monomers can vary greatly. Preferably, the amount of monomers other than the monomer M is such that a water-soluble copolymer P is obtained. According to the invention, the copolymer P is water-soluble. According to the invention, preferably, a majority by weight of anionic monomers is used to prepare the water-soluble copolymer P. Advantageously, the polymer P is soluble in any amount of water at room temperature, preferably at different pH values, in particular at pH values ​​of 2 to 12. According to the invention, preferably, the following substances can be used to prepare the polymer P:

[0025] - 2 to 100 wt. %, preferably 2 to 95 wt. % of monomers M, preferably monomers M are selected from monomers M1, monomers M2 and combinations thereof.

[0026] According to the present invention, more preferably, the following substances can be used to prepare the polymer P:

[0027] - 2 to 100 wt. %, preferably 2 to 95 wt. % of monomer M, preferably monomer M is selected from monomer M1, monomer M2 and combinations thereof, and

[0028] - 0 to 98 wt. %, preferably 5 to 98 wt. %, of a further monomer different from the monomer M, preferably the further monomer is selected from acrylic acid, methacrylic acid, ethyl acrylate, butyl acrylate and combinations thereof.

[0029] According to the present invention, the following materials can be used to prepare the polymer P:

[0030] - 2 to 100% by weight, preferably 2 to 95% by weight, of 2-acrylamido-2-methylpropanesulfonic acid, and

[0031] 0 to 98% by weight, preferably 5 to 98% by weight, of a further monomer different from the monomer M, preferably at least one further monomer selected from acrylic acid, methacrylic acid, ethyl acrylate, butyl acrylate and combinations thereof, in particular a combination of acrylic acid or methacrylic acid with ethyl acrylate or butyl acrylate.

[0032] According to the present invention, it is still further preferred that the following substances can be used to prepare the polymer P:

[0033] - 2 to 100% by weight, preferably 2 to 95% by weight, of styrene sulfonate, and

[0034] 0 to 98% by weight, preferably 5 to 98% by weight, of a further monomer different from the monomer M, preferably at least one further monomer selected from acrylic acid, methacrylic acid, ethyl acrylate, butyl acrylate and combinations thereof, in particular a combination of acrylic acid or methacrylic acid with ethyl acrylate or butyl acrylate.

[0035] During the polymerization reaction, a single monomer M is used, preferably a single monomer M1 or a single monomer M2, to obtain a homopolymer P1 according to the present invention. At least two different monomers M are used, preferably at least two different monomers M1 or monomers M2, or at least one monomer M and at least one other different monomer, preferably at least one other monomer M3 or monomer M4, to obtain a copolymer P2 according to the present invention. According to the present invention, homopolymer P1 and copolymer P2 can be used alone or in combination. Therefore, the composition T according to the present invention can contain at least one binder L selected from homopolymer P1, copolymer P2 and a combination thereof.

[0036] Preferably according to the invention, the polymerization is carried out at a temperature of above 30° C. and below 130° C., preferably below 100° C. or below 90° C. or below 80° C. or below 75° C. Preferably, during the polymerization for preparing the polymer P, the initiator compound is selected from peroxides (e.g. hydrogen peroxide), hydroperoxides (e.g. tert-butyl hydroperoxide), persulfates (e.g. sodium persulfate, ammonium persulfate, potassium persulfate), combinations thereof and their associations with metal salts, the metal salts being preferably selected from iron (e.g. Fe II or Fe III) salts, copper (e.g. Cu I or Cu II) salts and combinations thereof.

[0037] According to the invention, the polymer P is preferably prepared in a polar solvent, in particular in a solvent selected from the group consisting of water, alcohols, toluene, ketones, chlorinated solvents, esters and combinations thereof.

[0038] Also preferably according to the invention, the polymer P can be prepared in the presence of a chain transfer agent, preferably in the presence of a compound selected from isopropanol, mercaptans, dodecyl mercaptan, phosphorous acid, phosphites, hypophosphorous acid, hypophosphites, bisulfites, alkyl iodides, alkyl bromides and combinations thereof.

[0039] According to the present invention, polymer P may be unneutralized or it may be partially neutralized or completely neutralized. Preferably, polymer P is unneutralized or partially neutralized. According to the present invention, the carboxyl groups of polymer P may be partially neutralized at a ratio of 70 mol % to 97 mol %, preferably 90 mol % to 95 mol %. Polymer P may be partially neutralized or completely neutralized using at least one monovalent ion or at least one divalent ion. According to the present invention, polymer P may be partially neutralized or completely neutralized using a combination of at least one monovalent ion and at least one divalent ion. According to the present invention, polymer P may therefore be completely neutralized or partially neutralized with monovalent ions and divalent ions in a variable relative molar ratio. Preferably according to the present invention, the molar ratio of monovalent ions / divalent ions is 90 / 10 to 10 / 90 or 80 / 20 to 20 / 80, preferably 80 / 20 to 60 / 40, for example 70 / 30 or 50 / 50.

[0040] According to the present invention, primary amines, secondary amines or amines selected from K + 、Na + , Li + NH 4 + The monovalent ions or amines and their combinations are neutralized. The preferred monovalent ions are selected from Na + , Li + NH 4 + According to the invention, it is also possible to use a compound selected from the group consisting of Ca 2+ 、Zn 2+ Mg 2+and combinations thereof. Preferred divalent ions are Ca 2+ .

[0041] According to the present invention, the polymer P can be prepared using at least one selected from the group consisting of NaOH, KOH, LiOH, ammonium derivatives, ammonia, ammonium hydroxide, primary amines, secondary amines, CaO, Ca(OH) 2 、ZnO、Zn(OH) 2 、MgO、Mg(OH) 2 and combinations thereof. Particularly advantageously, when the composition T is used at a pH of less than 7, preferably at a pH of less than 5, the polymer P is neutralized with ammonia. According to the invention, the polymer P can be completely or partially neutralized with an amine base, for example a base selected from ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine, 1,6-hexanediamine, α,α′-phenylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, triethanolamine, aminomethylpropanol or 2-amino-2-methylpropanol (AMP) and combinations thereof.

[0042] It is preferred according to the invention that the pH of the polymer P is less than 12 or less than 11 or is between 2 and 12 or between 5 and 11. It is also preferred according to the invention that the pKa of the polymer P is less than 3.5 or is between 1.5 and 2.5.

[0043] The weight average molecular weight Mw of polymer P (measured by SEC) is from 2000 g / mol to 1000000 g / mol. Preferably, the weight average molecular weight Mw of polymer P (measured by SEC) is less than 800000 g / mol, less than 500000 g / mol, more preferably less than 300000 g / mol. The weight average molecular weight Mw of polymer P (measured by SEC) is generally greater than 5000 g / mol or greater than 15000 g / mol, preferably greater than 50000 g / mol or greater than 100000 g / mol.

[0044] The polydispersity index PI (measured by SEC) of the polymer P is typically less than 4 or is between 1.2 and 4 or between 1.5 and 4; between 1.2 and 3 or between 1.5 and 3; between 1.2 and 2.5 or even between 1.5 and 2.5.

[0045] According to the present invention, the molecular weight or molecular mass of the polymer P is determined by size exclusion chromatography (SEC). A test portion of the polymer solution corresponding to 90 mg of dry solid content is placed in a 10 mL flask. A mobile phase and 0.04% dimethylformamide (DMF) are added to a total mass of 10 g. The composition of the mobile phase is as follows: NaHCO 3 :0.05mol / L,NaNO 3:0.1mol / L,Triethanolamine:0.02mol / L,NaN 3 : 0.03 mass%. The SEC chain consists of the following devices: a Waters 510 isocratic pump with a flow rate set to 0.8 ml / min, a Waters 717+ sample changer, a column oven containing a Waters Guard Column Ultrahydrogel precolumn of 6 cm in length and 40 mm in inner diameter, followed by a Waters Ultrahydrogel linear column of 30 cm in length and 7.8 mm in inner diameter. Detection is provided by a Waters 410 RI differential refractometer. The column oven temperature is brought to 60°C and the refractometer temperature is brought to 45°C. The SEC device is calibrated using a series of sodium polyacrylate standards provided by PolymerStandards Service, with peak molecular weights ranging from 1000 g / mol to 1.10 6 The molecular weight of the samples was 250 g / mol and the polydispersity index was 1.4 to 1.7. The calibration curve was a straight line and took into account the correction obtained using the flow rate marker dimethylformamide (DMF). The acquisition and processing of the chromatograms were performed using the "PSS WinGPC Scientific" software v 4.02. The obtained chromatograms were incorporated into the region corresponding to molecular weights greater than 250 g / mol.

[0046] Typically, according to the invention, the binder L comprises the polymer P in particulate form.

[0047] According to the invention, the binder L preferably contains the polymer P in an amount of 5% to 100% by weight, preferably 10% to 70% by weight.

[0048] According to the invention, the essentially aqueous composition T comprises at least one binder L. Advantageously, the composition T according to the invention may not comprise other binders. Also advantageously, the composition T according to the invention may comprise at least one other binder different from the binder L, preferably an additional binder selected from (meth)acrylic polymers, comb polymers, carboxymethylcellulose (CMC), hydroxymethylcellulose, hydroxyethylcellulose, alginates, styrene-butadiene polymers, poly(allylamine, HCl), pullulan, copolymers of acrylic acid and acrylonitrile, and combinations thereof.

[0049] Advantageously also, the composition T according to the invention may also comprise at least one organic acid or at least one inorganic acid, preferably an acid chosen from sulfuric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, acetic acid and combinations thereof.

[0050] According to the invention, the substantially aqueous composition T comprises at least one material E. According to the invention, preferably, the composition T comprises a material E selected from silicon, lithium, carbon graphite or graphite carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, the material E being optionally doped with at least one element, preferably an element selected from lithium, germanium, silicon and combinations thereof. Preferred materials E are selected from carbon graphite, silicon and combinations thereof.

[0051] In particular, material E can be selected from conductive carbon compounds, furnace black, acetylene black, Ketjen carbonblack, carbon nanotubes (CNTs), synthetic graphite, natural graphite, hard carbon, activated carbon, carbon black, graphene, mesoporous carbon, amorphous silicon, semi-crystalline silicon, silicon oxide, silicon nanowires, tin, tin oxide, germanium, lithium titanate, materials suitable for use as negative electrodes of lithium-ion batteries, and combinations thereof.

[0052] According to the present invention, the material E may include a conductive material or a material capable of inserting lithium ions or capable of accepting lithium ions.

[0053] Advantageously according to the invention, the composition T may also contain other ingredients. In particular, the composition T according to the invention may also contain polyethylene, a fluorinated binder compound, for example selected from polyvinylidene fluoride (PVDF), poly(vinyl-pyrrolidone), polytetrafluoroethylene (PTFE), chlorotrifluoroethylene (ECTFE), polyethylenetetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), perfluoroalkoxylate (PFA), polychlorotrifluoroethylene (PCTFE), fluorinated acrylates, fluorinated silicones and combinations thereof.

[0054] The proportions of the components in the composition T may vary. Preferably, relative to the total weight of the binder L and the material E, the composition T according to the present invention comprises:

[0055] * 1 to 15% by dry weight of a binder L, and

[0056] * 85% to 99% dry weight of Material E.

[0057] The present invention also provides a method for preparing the composition T. The preparation method comprises:

[0058] - preparation of a binder L according to the invention,

[0059] - adding at least one material E, the material E is selected from metal fibers, metal particles, carbon graphite fibers, carbon graphite particles and combinations thereof, preferably, the material E is selected from silicon, lithium, carbon graphite or graphite carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, the material E is optionally doped with at least one element, preferably an element selected from lithium, germanium and combinations thereof.

[0060] The present invention also provides a method for producing a negative electrode using the composition T according to the present invention. The negative electrode production method comprises:

[0061] - applying at least one composition T according to the invention to a substrate,

[0062] - Drying and subsequent calendering of the coated substrate.

[0063] According to the present invention, preferably, a press is used for calendering, for example, at 0.1 t / cm 2 Up to 2t / cm 2 Under pressure, preferably at 0.2t / cm 2 Up to 1t / cm 2 under pressure.

[0064] Advantageously according to the invention, the substrate or current collector may be in the form of a plate, film, mesh, foam, sheet, rod, or any other form that does not significantly impair its ability to collect current. Typically, the substrate is in the form of a sheet, preferably copper metal (Cu 0 ) sheet or nickel metal (Ni 0 )piece.

[0065] Preferably, the present invention provides a production method according to the present invention, wherein the coating is carried out at a pH of less than 7 or at a pH of 4 to 6.5. Also preferably, the present invention also provides a production method according to the present invention, wherein the composition T is applied to the substrate by applying it to a thickness of less than 500 μm, preferably less than 100 μm or less than 50 μm on the metal surface after drying and calendering. Typically, according to the present invention, the thickness of the composition T applied to the substrate, dried and calendered is greater than 5 μm. According to the present invention, the composition T is applied to the substrate to a thickness of 20 μm to 30 μm after drying and calendering, the thickness being measured using a 1 μm to 1000 μm coating thickness gauge. Particularly preferably, the present invention provides a production method, wherein the coating of the composition T on the substrate is uniform. According to the present invention, the composition is uniformly coated when the particles of the material E are uniformly distributed in the layer. According to the present invention, the uniformity is measured by visual inspection by direct observation with the naked eye. According to the present invention, the coating is uniform when there are no visible aggregates on the surface of the layer when observed from the front in daylight.

[0066] Preferably, when producing a negative electrode according to the invention, at least one coating step is carried out at a pH of less than 7, preferably at a pH of less than 5.

[0067] The composition T according to the invention is applied by methods known per se. It can be applied by spraying, rolling, painting, gravure coating or any other method of applying an aqueous preparation to a surface.

[0068] The present invention enables production of a negative electrode using the composition T according to the present invention. Therefore, the present invention provides a negative electrode prepared by the production method according to the present invention.

[0069] According to the invention, particular, advantageous or preferred features of the composition T according to the invention define also particular, advantageous or preferred preparation methods, production methods and negative electrodes according to the invention.

[0070] The following examples illustrate various aspects of the invention.

[0071] Preparation and characterization of the binder L according to the invention comprising polymer P1a:

[0072] 50 g of a 50 wt % aqueous solution of sodium 2-acrylamido-2-methylpropanesulfonate (monomer M1b) and 850 g of deionized water were introduced into a 1 L glass reactor, where mechanical stirring and oil bath heating were performed. It was heated to 70 ° C. A solution containing 0.35 g of ammonium persulfate in 10 g of deionized water was subsequently poured in at one time. The temperature was maintained at 85 ° C for 120 minutes. After cooling to room temperature, the pH was adjusted to 6.0 by adding a 50 wt % aqueous solution of sodium hydroxide. This produced a binder L according to the present invention, which contained a homopolymer P1a having a weight average molecular weight Mw of 177000 g / mol measured by SEC at a concentration of 12 wt % in an aqueous solution.

[0073] Preparation and characterization of the binder L comprising polymer P1b according to the invention:

[0074] 165 g of sodium styrene sulfonate (monomer M1a) dissolved in 310 g of deionized water was introduced into a 1 L glass reactor with mechanical stirring and oil bath heating. It was heated to 85 ° C. A solution containing 0.7 g of ammonium persulfate in 10 g of deionized water was subsequently poured in at once. The temperature was maintained at 90 ° C for 90 minutes. After cooling to room temperature, the pH was adjusted to 8.5 by adding 50% by weight of aqueous sodium hydroxide solution. This produced a binder L according to the invention, which contained a homopolymer P1b with a weight average molecular weight Mw of 183500 g / mol measured by SEC at a concentration of 25% by weight in aqueous solution.

[0075] Preparation and characterization of the binder L comprising polymer P1c according to the invention:

[0076] 247 g of sodium styrene sulfonate (monomer M1a) dissolved in 464 g of deionized water were introduced into a 1 L glass reactor with mechanical stirring and oil bath heating. It was heated to 85 ° C. A solution containing 2.2 g of ammonium persulfate in 16 g of deionized water was subsequently poured in at once. The temperature was maintained at 90 ° C for 90 minutes. After cooling to room temperature, the pH was adjusted to 8.5 by adding 50% by weight of aqueous sodium hydroxide solution. This produced a binder L according to the invention, which contained a homopolymer P1c with a weight average molecular weight Mw of 108000 g / mol measured by SEC at a concentration of 33% by weight in aqueous solution.

[0077] Preparation and characterization of the binder L comprising the polymer P1d according to the invention:

[0078] 50 g of isopropanol and 150 g of deionized water were introduced into a 1 L glass reactor with mechanical stirring and oil bath heating. It was heated to 81° C. The following substances were then injected in parallel using 2 pumps over 120 minutes:

[0079] - a solution containing 20 g of ammonium persulfate in 30 g of deionized water,

[0080] - A solution comprising 243 g of sodium styrene sulfonate (monomer M1a) and 566 g of deionized water.

[0081] Subsequently, the isopropanol was separated by distillation. After cooling to room temperature, deionized water was added and the pH was adjusted to 8.3 by adding a 50% by weight aqueous sodium hydroxide solution. This produced a binder L according to the invention, which contained a homopolymer P1d having a weight-average molecular weight Mw of 10,000 g / mol measured by SEC at a concentration of 27% by weight in aqueous solution.

[0082] Preparation and characterization of the binder L according to the invention comprising polymer P2a:

[0083] 50g of 50% by weight aqueous solution of 2-acrylamido-2-methylpropanesulfonic acid sodium (monomer M1b), 60g of acrylic acid (monomer M3a), 15g of ethyl acrylate (monomer M4a) and 805g of deionized water were introduced into a 1L glass reactor, where mechanical stirring and oil bath heating were performed. It was heated to 70°C. A solution containing 0.35g of ammonium persulfate in 10g of deionized water was subsequently poured in at one time. The temperature was maintained at 85°C for 60 minutes. A solution containing 0.35g of ammonium persulfate in 10g of deionized water was poured in at one time again. The temperature was maintained at 85°C for 60 minutes. After cooling to room temperature, the pH was adjusted to 6.0 by adding 50% by weight of an aqueous solution of sodium hydroxide. This produced a binder L according to the present invention, which contained a copolymer P2a having a weight average molecular weight Mw of 158,000 g / mol measured by SEC at a concentration of 11.1% by weight in an aqueous solution.

[0084] Preparation and characterization of the binder L comprising polymer P2b according to the invention:

[0085] 75 g of acrylic acid (monomer M3a), 25 g of sodium styrene sulfonate (monomer M1a) and 805 g of deionized water were introduced into a 1 L glass reactor, where mechanical stirring and oil bath heating were performed. It was heated to 70 ° C. Subsequently, a solution containing 0.35 g of ammonium persulfate in 10 g of deionized water was poured in at one time. The temperature was maintained at 85 ° C for 60 minutes. A solution containing 0.35 g of ammonium persulfate in 10 g of deionized water was poured in at one time again. The temperature was maintained at 85 ° C for 60 minutes. After cooling to room temperature, the pH was adjusted to 6.3 by adding 50% by weight of aqueous sodium hydroxide solution. This produced a binder L according to the present invention, which contained a copolymer P2b with a weight average molecular weight Mw of 181000 g / mol measured by SEC at a concentration of 11.3% by weight in an aqueous solution.

[0086] Preparation and characterization of the binder L comprising the P2c polymer according to the invention:

[0087] 25 g of sodium styrene sulfonate (monomer M1a), 60 g of acrylic acid (monomer M3a), 15 g of ethyl acrylate (monomer M4a) and 830 g of deionized water were introduced into a 1 L glass reactor, where mechanical stirring and oil bath heating were performed. It was heated to 70 ° C. Subsequently, a solution containing 0.35 g of ammonium persulfate in 10 g of deionized water was poured in at one time. The temperature was maintained at 85 ° C for 60 minutes. A solution containing 0.35 g of ammonium persulfate in 10 g of deionized water was poured in at one time again. The temperature was maintained at 85 ° C for 60 minutes. After cooling to room temperature, the pH was adjusted to 5.8 by adding 50% by weight of aqueous sodium hydroxide solution. This produced a binder L according to the present invention, which contained a copolymer P2c with a weight average molecular weight Mw of 165000 g / mol measured by SEC at a concentration of 11.2% by weight in aqueous solution.

[0088] Preparation and characterization of the binder L comprising a P2d polymer according to the present invention:

[0089] 300 g of deionized water were introduced into a 1 L glass reactor with mechanical stirring and oil bath heating. It was heated to 94° C. The following substances were then injected in parallel using 2 pumps over 120 minutes:

[0090] - a solution containing 8 g of ammonium persulfate in 50 g of deionized water,

[0091] - A solution comprising 206 g of acrylic acid (monomer M3a), 36.4 g of sodium styrene sulfonate (monomer M1a) and 50 g of deionized water.

[0092] The temperature was maintained at 94° C. for 60 minutes. After cooling to room temperature, the pH was adjusted to 8.7 by adding a 50% by weight aqueous sodium hydroxide solution. This produced a binder L according to the invention comprising a copolymer P2d having a weight average molecular weight Mw of 26800 g / mol measured by SEC at a concentration of 38.5% by weight in aqueous solution.

[0093] Preparation of the aqueous negative electrode composition T according to the present invention

[0094] An aqueous composition comprising 5 dry % polymer P2a and 5 dry % carbon black (Black C65 "Imerys") was prepared with binder L comprising polymer P2a (11.1 wt %), stirring at 3000 rpm for 2 hours using a stirrer equipped with a 40 mm disk wheel.

[0095] Subsequently, 0.32 g of this aqueous composition of carbon black and P2a polymer, 1.2 g of silicon particles (SI-100 30 nm to 50 nm, "Get Nano Materials") and deionized water were introduced into a glass beaker and stirred at 4500 rpm for 2 hours using a stirrer equipped with a 25 mm disc wheel. 6.32 g of a graphite mixture (92.5 wt. % GHDR, 5 wt. % SFG15L, 2.5 wt. % KS6L, "Imerys") and deionized water were added. Stirring was continued for 1 hour. Subsequently, 0.4 g of styrene-butadiene binder latex (SNR BM-451B "Zeon" latex, 40 wt. %) was added and stirred at 500 rpm for 30 minutes. The amount of water added was defined to obtain an aqueous negative electrode composition T2a according to the invention, the final concentration of which was 44.6 dry weight %.

[0096] Aqueous negative electrode compositions T2b to T2d according to the present invention were prepared in a similar manner, and their final concentrations were also 44.6% by dry weight. They respectively contained the binder L containing copolymers P2b to P2d according to the present invention.

[0097] Production and characterization of the negative electrode according to the invention

[0098] A 100 μm thick copper sheet was coated with a 20 μm thick layer of the composition T1a according to the invention using a manual coating rod. A 15 mm diameter disc was cut using a precision cutter. The coated disc was calendered at 0.6 t / cm2 using a calender. The disc was then dried in an oven and gradually heated to 110° C. for 18 hours under vacuum.

[0099] After cooling to room temperature, the homogeneity of the layer was assessed by visual inspection: when viewed from the front in daylight, the surface of the layer had no visible aggregates or no visible surface unevenness.

[0100] The density of the resulting negative electrode was then measured by weighing on a balance, and its porosity was subsequently calculated.

[0101] Negative electrodes were similarly prepared and characterized using aqueous negative electrode compositions T2b to T2d.

[0102]

[0103] Table 1

[0104] Therefore, the aqueous negative electrode composition containing the binder according to the present invention can prepare a stable negative electrode, and the active material is well combined with the copper layer. The negative electrode composition according to the present invention can prepare a negative electrode with a uniform layer. Therefore, these negative electrodes can be easily used to produce rechargeable batteries or secondary batteries.

[0105] Production and characterization of half-cells comprising a negative electrode according to the invention

[0106] Keep in an inert atmosphere (Ar, O 2 and H 2 O<0.5ppm) in a glove box ("MBraun LabStar"), the electrolyte ("Solvionic" 1M, LiPF 6 in an ethylene carbonate-ethyl methyl carbonate mixture with 2% ethylene carbonate and 10% fluoroethylene carbonate), a negative electrode according to the present invention, a pre-cut lithium disc (diameter 15.6 mm, thickness 0.25 mm), a separator disc ("Whatman" GF / C 1822-849, diameter 17 mm, thickness 0.26 mm, pore size 1.2 µm) and a separator disc ("Celgard" 2325 three-layer PE / PP / PE) were assembled on the working electrode.

[0107] A half-cell comprising a negative electrode according to the present invention prepared with aqueous negative electrode composition T2a was subjected to charge-discharge cycles in a constant temperature chamber at 25° C.:

[0108] - 2 cycles: C / 7 discharge to 0.005V, C / 100 cut-off, then C / 7 charge to 1.0V cut-off,

[0109] - 3 cycles: C / 5 discharge to 0.005V, C / 50 cut-off, then C / 5 charge to 1.0V cut-off,

[0110] - 102 cycles: 1C discharge to 0.005V, C / 40 cut-off, then 1C charge to 1.0V cut-off.

[0111] A half-cell containing a negative electrode according to the present invention having an aqueous negative electrode composition T2b to an aqueous negative electrode composition T2d was similarly prepared and characterized. The charge (load), capacity, initial coulombic efficiency (ICE), coulombic efficiency after 10 cycles and coulombic efficiency after 20 subsequent cycles (CE10, CE20), coulombic cycling efficiency (coulombiccycling efficiency)-CCE1, capacity retention after 10 cycles relative to the first cycle, and capacity retention after 20 cycles relative to the first cycle (CR10, CR20) of each half-cell were determined. The results are shown in Table 2.

[0112]

[0113] Table 2

[0114] The binder according to the present invention enables the preparation of an aqueous negative electrode composition that is highly effective in obtaining a negative electrode and a battery having a high silicon concentration and whose electrochemical properties are particularly interesting.

Claims

1. An aqueous negative electrode composition T, relative to the total weight of a binder L and a material E, comprising: * 0.5 to 15% by dry weight of at least one binder L comprising at least one water-soluble polymer P having a weight average molecular weight Mw (measured by SEC) of 2000 to 1000000 g / mol, said water-soluble polymer P being prepared by polymerization of at least one organic sulfur monomer M in the presence of at least one initiator compound, and * 85% to 99.5% by dry weight of at least one material E selected from metal fibers, metal particles, carbon graphite fibers, carbon graphite particles, silicon particles, and combinations thereof.

2. The composition T according to claim 1, wherein the monomer M is selected from the group consisting of sulfonated monomers M1, M2 and combinations thereof, or wherein only monomer M is used in the preparation of the polymer P; preferably, the organosulfur monomer M is selected from the group consisting of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), allylsulfonic acid, alkylenesulfonates, alkylenearylsulfonates, in particular styrenesulfonates, vinylsulfonates, methallylsulfonates, allylsulfonates, methallylsulfonates, allylsulfonates, methallylsulfates, allylsulfates, 2-sulfoethylmethacrylate, 3-allyloxy-2-hydroxy-1-propanesulfonic acid, 3-sulfopropylmethacrylate, salts thereof and combinations thereof.

3. The composition T according to any one of claims 1 or 2, wherein: - monomer M in combination with at least one other anionic monomer M3 selected from acrylic acid, methacrylic acid, acrylates, methacrylates, maleic acid, maleates, itaconic acid, itaconic acid salts, crotonic acid, crotonates, acrylic acid oligomers and combinations thereof, or - monomer M in combination with at least one other nonionic monomer M4 selected from vinyl acetate, C1 to C8 esters of compounds derived from an acid selected from acrylic acid, methacrylic acid, maleic acid, itaconic acid and crotonic acid (e.g. ethyl methacrylate, methyl methacrylate, butyl methacrylate, ethyl acrylate, methyl acrylate, butyl acrylate), hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxypropyl acrylate, amino monomers (e.g. acrylonitrile, vinyl-lactam), styrene and combinations thereof, or - Prepare polymer P using: - 2 to 100 wt. %, preferably 2 to 95 wt. % of monomer M, preferably monomer M is selected from monomer M1, monomer M2 and combinations thereof, and - 0 to 98% by weight, preferably 5 to 98% by weight, of a further monomer different from the monomer M, preferably the further monomer is selected from the group consisting of the monomer M3, the monomer M4 and a combination thereof, or - the polymer P is prepared in the presence of at least one initiator compound selected from peroxides (e.g. hydrogen peroxide), hydroperoxides (e.g. tert-butyl hydroperoxide), persulfates (e.g. sodium persulfate, ammonium persulfate, potassium persulfate), combinations thereof and their associations with metal salts, preferably the metal salt is selected from iron (e.g. Fe II or Fe III) salts, copper (e.g. Cu I or Cu II) salts and combinations thereof, or - the polymer P is prepared in the presence of at least one chain transfer agent, preferably in the presence of a compound selected from isopropanol, mercaptans, dodecyl mercaptan, phosphorous acid, phosphites, hypophosphorous acid, hypophosphites, bisulfites, alkyl iodides, alkyl bromides and combinations thereof, or - the polymer P is not neutralized, or the polymer P is partially neutralized or fully neutralized, preferably with at least one compound selected from the group consisting of NaOH, KOH, LiOH, ammonium derivatives, ammonia, ammonium hydroxide, primary amines, secondary amines, CaO, Ca(OH)2, ZnO, Zn(OH)2, MgO, Mg(OH)2 and combinations thereof, or - the pH of the polymer P is less than 12 or less than 11 or is between 2 and 12 or between 5 and 11, or - The pKa of polymer P is less than 3.5 or is between 1.5 and 2.

5.

4. The composition T according to any one of claims 1 to 3, wherein: - the weight average molecular weight Mw of the polymer P (measured by SEC) is less than 800,000 g / mol, less than 500,000 g / mol, more preferably less than 300,000 g / mol, or The weight average molecular weight Mw of the polymer P (measured by SEC) is greater than 5000 g / mol or greater than 15000 g / mol, preferably greater than 50000 g / mol or greater than 100000 g / mol.

5. The composition T according to any one of claims 1 to 4, comprising at least one binder L chosen from homopolymers P1, copolymers P2 and combinations thereof.

6. Composition T according to any one of claims 1 to 5, comprising at least one organic acid or at least one inorganic acid, preferably the acid is selected from sulfuric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, acetic acid and combinations thereof.

7. The composition T according to any one of claims 1 to 6, wherein the material E is selected from silicon, lithium, carbon graphite or graphite carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, and the material E is optionally doped with at least one element, preferably an element selected from lithium, germanium and combinations thereof.

8. The composition T according to any one of claims 1 to 7, which does not contain other binders or further contains at least one other binder different from agent L, preferably, the other binder is selected from (meth)acrylic polymers, comb polymers, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, alginates, styrene-butadiene polymers, poly(allylamine, HCl), pullulan and combinations thereof.

9. The composition T according to any one of claims 1 to 8, further comprising polyethylene, a fluorinated bonding compound, for example a compound selected from polyvinylidene fluoride (PVDF), poly(vinyl-pyrrolidone), polytetrafluoroethylene (PTFE), chlorotrifluoroethylene (ECTFE), polyethylenetetrafluoroethylene (ETFE), fluorinated ethylene propylene (FEP), perfluoroalkoxylate (PFA), polychlorotrifluoroethylene (PCTFE), fluorinated acrylates, fluorinated silicones and combinations thereof.

10. The composition T according to any one of claims 1 to 8, comprising, relative to the total weight of the binder L and the material E: * 1 to 15% by dry weight of a binder L, and * 85% to 99% dry weight of Material E.

11. A method for preparing an aqueous composition T according to any one of claims 1 to 10, comprising: - preparing a binder L according to any one of claims 1 to 6, - adding at least one material E selected from metal fibers, metal particles, carbon graphite fibers, carbon graphite particles and combinations thereof, preferably, the material E is selected from silicon, lithium, carbon graphite or graphite carbon, hexagonal carbon, rhombohedral carbon and combinations thereof, the material E is optionally doped with at least one element, preferably an element selected from lithium, germanium and combinations thereof.

12. A method for producing a negative electrode, comprising: - applying at least one composition T according to any one of claims 1 to 10 to a substrate, - Drying and subsequent calendering of the coated substrate.

13. The production method according to claim 12, wherein: - the coating is carried out at a pH less than 7 or at a pH between 4 and 6.5, or - coating the composition T on a substrate to a thickness after drying and calendering of less than 500 μm, preferably less than 100 μm or less than 20 μm, as measured using a coating thickness gauge of 1 μm to 1000 μm, or - applying the composition T to a substrate to a thickness after drying and calendering greater than 5 μm, the thickness being measured using a coating thickness gauge of 1 μm to 1000 μm, or - The application of composition T on the substrate is uniform.

14. A negative electrode prepared according to the production method according to claim 12 or 13.

Citation Information

Patent Citations

  • Paste composition for negative electrode for lithium-ion rechargeable battery, composite particles for negative electrode for lithium-ion rechargeable battery, slurry composition for negative electrode for lithium-ion rechargeable battery, negative electrode for lithium-ion rechargeable battery, and lithium-ion rechargeable battery

    EP3214676A1

  • Negative electrode for secondary cell, secondary cell, slurry composition, and manufacturing method

    WO2014024937A1

  • Binder composition for storage device, slurry for storage device, electrode for storage device, separator, and storage device

    WO2015008626A1